Pengaruh Strategi Harga dan Kualitas Layanan dengan Preferensi Pembelian Pelanggan di Platform E-commerce Shopee - Henri Yawan; Akmal Ramadhan Putra Setiawan; Muhammad Naufal Nurfirmansyah; Muhammad Fadli Al-Multazim; Noor Kholis Budiman; Adi Prehanto; Asep Nuryadin (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study examines the impact of pricing strategy and service quality on customer preferences on the Shopee e-commerce platform. This study's methodology, which included a quantitative approach and primary data from a questionnaire, identified 33 Shopee users in Tasikmalaya. An analysis using SPSS confirms that the two factors mentioned above—price strategy and service quality—contribute about 40.5% to consumers' preferences for fashion products on Shopee. Even though price strategy has a significant relationship, service quality has a stronger and more positive impact on customer preferences. Implicitly, it is crucial for e-commerce businesses to improve the quality of their services while meticulously developing price phase strategy to make it more in line with customer preferences. All of this offers advantages for the e-commerce business in developing strategies to meet customer needs in an increasingly competitive market.